Variation of rice starch structure and physicochemical properties in response to high natural temperature during the reproductive stage - Tu, Debao; Jiang, Yang; Salah, Akram; Xi, Min; Cai, Mingli; Cheng, Bo; Sun, Xiaosong; Cao, Cougui; Wu, Wenge (Frontiers in Plant Science, 2023)
Climate warming affects rice growth at different phenological stages, thereby increasing rice chalkiness and protein content and reducing eating and cooking quality (ECQ). The structural and physicochemical properties of rice starch played important roles in determining rice quality. However, differences in their response to high temperature during the reproductive stage have been rarely studied. In the present study, they were evaluated and compared between two contrasting natural temperature field conditions, namely, high seasonal temperature (HST) and low seasonal temperature (LST), during the reproductive stage of rice in 2017 and 2018. Compared with LST, HST significantly deteriorated rice quality, including increased grain chalkiness, setback, consistence, and pasting temperature and reduced taste values. HST considerably reduced the total starch and increased the protein content. Likewise, HST significantly reduced the short amylopectin chains [degree of polymerization (DP) <12] and increased the long amylopectin chains (DP > 12) and relative crystallinity. The starch structure, total starch content, and protein content explained 91.4%, 90.4%, and 89.2% of the total variations in pasting properties, taste value, and grain chalkiness degree, respectively. In conclusion, we suggested that rice quality variations were closely associated with the changes in chemical composition content (total starch and protein content) and starch structure in response to HST. These results indicated that we should improve the resistance of rice to high temperature during the reproductive stage to improve the fine structure of rice starch in further breeding and practice.